The Quality Culture Model of Private Vocational Education Institutes - Sinprasong, Kannaporn; Wangthanomsak, Mattana (Journal of Humanities and Social Sciences Thonburi University, 2022)
The purposes of this research were to determine the components of the quality culture of private vocational education institutes and the causal relationship of the quality culture model of private vocational education institutes which applied Exploratory Factor Analysis to be the instrument. For data collecting, there were a semi-structured interview and opinionnaire. The sample consisted of 209 private vocational education institutes from entire region by stratified random sampling. There were 2 respondents from each institute: 1 director or assistant director and 1 head or responsible person of Education Quality Assurance department with a total 418 respondents. The statistics for analyzing the data were frequency, percentage, arithmetic means, standard deviation, exploratory factor analysis, path analysis and content analysis. The results revealed that the factors of the Quality Culture of private vocational education institutes includes 5 components which were 1) Educational Management Quality Development Plans 2) Rewards for Team Development 3) Visionary Leadership Encouragement 4) Quality Operational Guidelines and 5) Organizational Loyalty Building. The relationship between every component was found at .01 level of statistical significance and the model of the quality culture of private vocational education institutes fitted in with the empirical data.